Antioxidant and Antibacterial Potential of Silver Nanoparticles: Biogenic Synthesis Utilizing Apple Extract. (28th November 2016) - Nagaich, Upendra; Gulati, Neha; Chauhan, Swati
Abstract : The advancement of the biological production of nanoparticles using herbal extracts performs a significant role in nanotechnology discipline as it is green and does not engage harsh chemicals. The objective of the present investigation was to extract flavonoids in the mode of apple extract and synthesize its silver nanoparticles and ultimately nanoparticles loading into hydrogels. The presence of flavonoids in apple extract was characterized by preliminary testing like dil. ammonia test and confirmatory test by magnesium ribbon test. The synthesized silver nanoparticles were characterized using UV spectroscopy, particle size and surface morphology, and zeta potential. Silver nanoparticles loaded hydrogels were evaluated for physical appearance, pH, viscosity, spreadability, porosity, in vitro release, ex vivo permeation, and antibacterial ( E. coli and S. aureus ) and antioxidant studies (DPPH radical scavenging assay). Well dispersed silver nanoparticles below were observed in scanning electron microscope image. Hydrogels displayed in vitro release of 98.01% ± 0.37% up to 24 h and ex vivo permeation of 98.81 ± 0.24% up to 24 h. Hydrogel effectively inhibited the growth of both microorganism indicating good antibacterial properties. The value of percent radical inhibition was 75.16% ± 0.04 revealing its high antioxidant properties. As an outcome, it can be concluded that antioxidant and antiageing traits of flavonoids in apple extract plus biocidal feature of silver nanoparticles can be synergistically and successfully utilized in the form of hydrogel.